2006
DOI: 10.7863/jum.2006.25.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Gray Scale Contrast Enhancement and Quantification in Different Positions of Rabbit Liver

Abstract: Flow parameters are different between central and ventral peripheral positions and between left and right lobes of hepatic parenchyma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Here, we correlated the liver CEUS perfusion derived parenchyma and PV PSI and PIT with histology in CHC patients stratified according to their liver histological fibrosis score. In accordance with previously published data by Li et al (2006), our data showed that PV PSI was constantly higher than LP PSI values in all fibrosis stages. In our study, we found no correlation between PV PSI values and fibrosis scores.…”
Section: Discussionsupporting
confidence: 93%
“…Here, we correlated the liver CEUS perfusion derived parenchyma and PV PSI and PIT with histology in CHC patients stratified according to their liver histological fibrosis score. In accordance with previously published data by Li et al (2006), our data showed that PV PSI was constantly higher than LP PSI values in all fibrosis stages. In our study, we found no correlation between PV PSI values and fibrosis scores.…”
Section: Discussionsupporting
confidence: 93%
“…The PSI in the portal vein is higher than that in the liver parenchyma at every assessment stage, supporting Li J's results [11]. As the fibrosis developed, a progressive reduction of parenchyma PSI was observed in the late phase, which is accordance with Kaneko T's studies with Levovist [2], but did not occur with PV PSI, accordingly the gap between PV and parenchyma PSI is increased.…”
Section: Discussionsupporting
confidence: 82%
“…A weakness in the study was the small number of animals and injections used to calculate perfusion parameters. Results obtained from contrast‐enhanced ultrasound is influenced by machine‐, 17,19,23,24 contrast agent‐ 7,17,23,30 and patient‐related factors 7,17,19,23,31,32 . The injection protocol and technique was also partially responsible for the observed variation, because bubble concentration and size can vary from injection to injection, and from vial to vial, in a bolus study.…”
Section: Discussionmentioning
confidence: 99%